Dampak Pandemi Covid-19 Terhadap Volume Ekspor Dan Impor Beras Di Indonesia - Sahputra, Eka; Hasanuddin, Hasanuddin; Sari, Romida Rifiana; Eviatun, Esti (LPPM Institut Bisnis dan Informatika Kesatuan, 2021)
This research aims to see the influence of the Covid-19 pandemic on the volume of exports and imports of Indonesian rice commodities compared to the period before the Covid-19 pandemic using data for three years before the Covid-19 pandemic was officially announced in Indonesia. This research uses a library study method by using data collected and then studying and reading several library sources via electronic media. The library sources used in this paper are scientific journals and secondary sources in the form of data that has been processed by government agencies. The results of this research show that there was a decrease in the average volume of exports and imports of Indonesian rice commodities during the Covid-19 pandemic which was caused by restrictions on the mobility of goods and services entering from abroad as part of the implementation of health protocols. Keywords : Covid-19, Ekspor, Impor